The Role of Perceived Authoritative Parenting Style towards The Resilience of Young Adults in Indonesia - Christy Clarissa Wibisono; Aliyaturrahmah Supriyadi (Developmental and Clinical Psychology, 2025)
Resilience, a protective factor against the increasing risk of young adults’ mental health, is found to be decreasing in Indonesia. On the other hand, parenting styles are found to be one of the factors influencing resilience. As the most effective parenting style for children’s development, this study examines the role of perceived authoritative parenting style towards the resilience of young adults in Indonesia. This research was done with 171 young adults between 18 to 25 years old in Indonesia who filled out the self-report instruments for this study: the Resiliency Scale for Young Adults (RSYA), and the Parenting Style Circumplex Inventory (PSCI). With simple linear regression analysis, the results indicated that the father’s perceived authoritative parenting style significantly predicts resilience (F (1, 169) = 30.2, p < .001), by having a positive and significant relationship with it. Mother’s perceived authoritative parenting is also found to predict resilience (F (1, 169) = 27.4, p < .001), with a positive and significant relationship. The presence of behavioral control, warmth, and support, including autonomy-granting that authoritative parents implement, potentially contribute to the increase of children’s resilience, which is advised to be implemented by parents. Additionally, this research is expected to provide new references for future research regarding this topic.